Soy Saponins Meditate the Progression of Colon Cancer in Rats by Inhibiting the Activity of β-Glucuronidase and the Number of Aberrant Crypt Foci but Not Cyclooxygenase-2 Activity. (2nd October 2013) - Guo, Yu-Wei; Chen, Yue-Hwa; Chiu, Wan-Chun; Liao, Hsiang; Lin, Shyh-Hsiang
Abstract : Objective . The effect of extracted crude soybean saponins on preneoplastic lesions, aberrant crypt foci (ACF), and the related mechanism were investigated. Research Methods and Procedures . Rats were assigned into five groups according to different doses of extracted crude soybean saponins and received 1, 2-dimethylhydrazine (DMH) injection in week 5. In week 15, all rats were sacrificed. The number of ACFs, the cyclooxygenase-2 (COX-2) protein expression, the level of prostaglandins E2 (PGE2), and the activity of β -glucuronidase were examined. Results . Results revealed that the consumption of extracted crude soybean saponins decreased the number of ACFs and the activity of β -glucuronidase in rats, while the expression of COX-2 protein and PGE2 level were not affected. Conclusions . Soybean saponins were effective in inhibiting colon cancer by downregulating the activity of β -glucuronidase in colonic mucosa but not the COX-2 protein expression and PGE2 level.